"Undatable, unattractive, redundant"? The Rapavi silcrete source, Saint-Pierre-Eynac (Haute-Loire, France): Challenges studying a prehistoric quarry-workshop in the Massif Central mountains. (October 2017) - Wragg Sykes, R.M.; Delvigne, V.; Fernandes, P.; Piboule, M.; Lafarge, A.; Defive, E.; Santagata, C.; Raynal, J.P.
Abstract: Silcretes are not widely discussed archaeologically as a prehistoric lithic resource in Europe, despite there being many years of geological research into their formation, and in some regions, a long record of their use in prehistory. In the Massif Central, south eastern France, various silcrete sources represent some of the largest and best quality siliceous stone sources within this otherwise volcanic area. Field research within a wider programme of landscape archaeology and lithic sourcing identified a quarry-workshop for one of these silcrete sources, at Rapavi, Saint-Pierre-Eynac (Haute-Loire). Archaeological and geological results are reported, discussing the technological behaviour uncovered at this locale and its wider regional connections, including the presence of imported flint artefacts. Additionally, the Rapavi silcrete provides an example of the challenges encountered when analysing raw materials with idiosyncratic fracture properties, and attempting to disentangle quarry-workshop palimpsests. Highlights: Identification of a silcrete source and prehistoric quarry-workshop in Massif Central, France. Summary of fieldwork 2013–2015 including excavation. Analysis of lithic assemblage showed primarily informal technological strategies. Multiple exotic flint materials identified, imported from < 70 km. Synthesis of the export and use of the silcrete in regional archaeological assemblages, and assessment of its importance.